Design a smart classroom based on Arduino - Maulana, Hussain Rizqi; Rosdiana, R (Geuthèë Institute, 2024)
The rapid pace of technology and human activities in the modern era often causes people to become negligent in small matters, one of which is saving electricity, including being negligent in the use of electronic devices and in managing electrical equipment. The Arduino-based Smart Classroom is a device-assisted system. devices that are obtained automatically and can be programmed via a computer system that are applied to campus buildings or conventional classes which aim to overcome human negligence and create practicality in terms of attendance in class both in campus and school environments. The control system used in this research is Arduino UNO with the help of several components such as PIR, RFID, and RTC sensors as input, and the output system is lights, sockets, I2C LCD, and Google Spreadsheet. So the research results show that the design the tools and systems have been built and in the application this tool will function when someone enters the class, the lights and sockets as electricity distribution components will turn on automatically and along with automatic attendance where the absence of attendance data will be recorded in Google Spreadsheet. From the results When testing this tool, research results showed that the lights and sockets could turn on and off automatically when people entered and left the classroom... and so did automatic attendance which successfully sent data to Google Spreadsheet.